2021
DOI: 10.3390/atmos12080991
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sea-Surface Roughness Length at a Coastal Site

Abstract: Sea-surface roughness length is a key parameter for characterizing marine atmospheric boundary layer. Although aerodynamic roughness lengths for homogeneous land and open water surfaces have been examined extensively, the extension of relevant knowledge to the highly inhomogeneous coastal area is problematic due to the complex mechanisms controlling coastal meteorology. This study presented a lidar-based observational analysis of sea-surface roughness length at a coastal site in Hong Kong, in which the wind da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The higher roughness of the urban terrain was also responsible for larger spatial and temporal variations in the wind field, which resulted in higher turbulence. The opposite was true for winds coming from the sea (WDs between 0 and 240 deg) because of the lower roughness of the sea surface [44]. It is known that lower roughness is directly related to higher wind speeds [45].…”
Section: Global Statisticsmentioning
confidence: 98%
“…The higher roughness of the urban terrain was also responsible for larger spatial and temporal variations in the wind field, which resulted in higher turbulence. The opposite was true for winds coming from the sea (WDs between 0 and 240 deg) because of the lower roughness of the sea surface [44]. It is known that lower roughness is directly related to higher wind speeds [45].…”
Section: Global Statisticsmentioning
confidence: 98%
“…In NWP models, interactions between wind and waves are simulated through drag coefficients or roughness length parameterizations. Numerous studies have shown key role of precise roughness length parameterization in accurately computing surface fluxes over the sea [e.g., 8,9]. In most NWP models, the sea surface is considered a smooth surface, but the sea surface constantly changes due to the propagation of waves with different amplitudes.…”
Section: Introductionmentioning
confidence: 99%